Marine Le Pen, the Rassemblement National and breaking the 'glass ceiling'? The 2022 French presidential and parliamentary elections. (2nd October 2022) - Startin, Nicholas
ABSTRACT: The 2022 French Presidential elections produced a re-run of the 2017 contest with Marine Le Pen and Emmanuel Macron in a head-to-head run-off in the second round with the Radical Right, Rassemblement National (RN) challenger unable to defeat the incumbent President. At the subsequent Parliamentary elections, the RN made a significant breakthrough, piercing the so-called 'plafond de verre' ('Glass Ceiling'), obtaining 89 seats, a tenfold increase compared to 2017. The article analyses the causes of this breakthrough by concentrating predominantly on the 'external supply-side' conditions created by the RN under Marine Le Pen's leadership during the Macron presidency and in the 2022 election campaigns. It also focuses on Le Pen's responses to the significant internal challenges faced within the party and subsequently from Far-Right contender Eric Zemmour during the campaign. The article concludes that the 'supply-side' responses emanating from Le Pen and the RN are crucial to a holistic understanding of the party's ability to crack the 'plafond de verre' at the 2022 Parliamentary elections.